Pengaruh Kelengkapan Produk Dan Harga Terhadap Keputusan Pembelian Di Warung Klontong Madura Toko Fahmi - Masyhuri, Mohammad Nur Faizi; Khalikussabir, Khalikussabir; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The objective of this research is to decide the influence of Product Completeness and Price on Purchase Decisions at Madura Grocery Store Toko Fahmi among FEB students. The sample used in this study consists of 60 students. The data collection technique employed in this research is a questionaire, and the bata analysys methud used is mutltiple liniear regeression analiysis. The qesults of this study indicatee that Product Completeness and Price have a significant impact on Purchase Decisions at Madura Grocery Store. Keywords: Product Completness, Price, Purchase Decision, Madura Grocery Store